ANALYSIS OF FLAME RETARDANT FOR COVER ELECTRICAL PLASTIC INJECTION USING MATERIAL POLYPROPYLENE - Muhammad Yusuf Nurfani (Asosiasi Dosen Muda Indonesia, 2022)
Injection is manufacturing process for make a product using thermoplastic material, critical part for electric normally should be self-protecting from fire. Flame Retardant (FR) is a type of thermoplastic material that is resistant to fire and can to mixed additive between resin plastic. Application of FR on various types of plastic resins such as polypropylene (PP). This study discusses the analysis of flame retardant for cover electrical using material polypropylene and benzene additive compound. This study shows that PP and benzene can mixed for create FR grade for application injection plastic. In the physical structure this material has a crack after scanning ×10,000. that elongation of material has a different in some temperature, for 30 ◦C elongation of material is 50%, for 60 ◦C elongation material is 60% and for 90◦C elongation about 90%. Heat capacity of material average in 2700J/kg◦C. average of drop time fire in cover electric average is 1,12 second.